A pedagogia das competências: estudo de caso em um curso de tecnologia da UTFPR - Boschetti, Luís Paulo Zanolla [UNESP] (2014)
Comprising two chapters, this dissertation discusses, in its first chapter, on the pedagogy of competences, exposing opinions of its intellectual mentor, Philippe Perrenoud, and five Brazilian authors with opposing views, among which Acacia Zeneida Kuenzer and Marise Nogueira Ramos. The second chapter is devoted to a brief historical account of the Federal Technological University of Paraná (UTFPR), it is followed by a clearance (under the point of view of the pedagogy of competences) of the undergraduate course of Technology in Industrial Maintenance, offered on the campus Medianeira (PR). The profile of teachers, students and graduated, the legislation relating thereto and the regional labor market were also analyzed. It was concluded that, despite the clear institutional ideological orientation in favor of the pedagogy of competences (evidenced by internal regulations), the profiles of the student and graduate follow much more the fordist/taylorist paradigm than the toyotism, for the reasons listed in throughout the text.